2009
DOI: 10.1128/iai.01170-08
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Infection Can Reduce Insulitis and Type 1 Diabetes through CD25- and IL-10-Independent Mechanisms

Abstract: Parasitic helminth infection has been shown to modulate pathological inflammatory responses in allergy and autoimmune disease. The aim of this study was to examine the effects of infection with a helminth parasite, Heligmosomoides polygyrus, on type 1 diabetes (T1D) in nonobese diabetic (NOD) mice and to elucidate the mechanisms involved in this protection. H. polygyrus inoculation at 5 weeks of age protected NOD mice from T1D until 40 weeks of age and also inhibited the more aggressive cyclophosphamide-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 48 publications
8
111
2
Order By: Relevance
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, clinical trials in humans examining effects of helminth products on disease severity in autoimmune diseases have shown promising results, as well as showing the safety of these helminth-derived immunomodulators for use as therapeutic agents. Although there is evidence to show that helminth infection can prevent T1DM in mice, 11,13,[23][24][25] there are no reports to support this hypothesis in humans. Epidemiologic studies carried out in southern India have shown reduced prevalence of LF after mass drug administration.…”
Section: Discussionmentioning
confidence: 88%
“…10 Experimentally, a number of helminthic parasites, including the trematode Schistosoma mansoni 11 and the nematodes Litomosoides sigmodontis, Heligmosomoides polygyrus, and Trichinella spiralis , prevent the onset or suppress the severity of T1DM in non-obese diabetic mice. 12,13 Several studies have found that persons infected with chronic parasitic worm infections have lower rates of autoimmune diseases than persons without these infections. 14,15 Currently, trials are under way using Trichuris suum and Necator americanus infection for the treatment of T1DM, multiple sclerosis, inflammatory bowel disease, asthma, and food allergies.…”
Section: Introductionmentioning
confidence: 99%
“…1C, 1D). Although separated, the spleen and the gut are still in relative proximity, and Th2 responses to H. polygyrus can be detected in the spleen (28). To increase the distance between the site of worm infestation and the secondary infection, we delivered BCG in the footpad.…”
Section: H Polygyrus Infection Impairs Priming Of Mycobacteria-specimentioning
confidence: 99%
“…This protective effect could also be adoptively transferred with either regulatory T (Treg) cell [31], or B-cell transfer [32], in both cases in an IL-10 independent manner. Together with a number of other studies on H. polygyrus infection in allergy [33,34], colitis [35][36][37] and diabetes [38,39], it is clear that this helminth downregulates multiple effector pathways of the adaptive immune response [40].Therapy of human immune pathologies with live helminth parasites continues to be evaluated, but will remain an empirical process. Moreover, permitted doses of live parasites are minimal due to ethical and logistical constraints [41], such that exposure levels and duration do not approach those seen in endemic populations.…”
mentioning
confidence: 99%